Performance of a simplified model inner-tube biodigester for biomethane production for household use in Nigeria - Suleiman, A. I.; Kevin, L. W. H.; Ajayi, A. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
In the developing countries, methane capture from manures has been encouraged by using biogas plants which are predominantly household anaerobic digesters handling manure of livestock held by an average-sized family. This paper aims to assess the performance of a simplified model inner tube biodigester for biomethane production for household use in Nigeria. This paper also evaluates the biomass conversion technologies tested in the REEF (Renewable Energy Engineering Facility) Lab at the University of Exeter, the UK and the technology readiness level and implementation in Nigeria. Cow slurry and Inoculum were used to evaluate the operational efficiency and feasibility of the model Inner tube digester, with the aim of encouraging its use and adoption in Nigeria and Africa in general to help impact on the Sustainable Development Goals (SDG) on Climate Change and Energy Efficiency targets. The model digester as an option against the use of firewood, Kerosene or Liquid Petroleum Gas (LPG) system could increase the renewable energy potential in Nigeria while retaining organic matter and nutrients for soil replenishment for agricultural purposes. The 12-litre scale Biodigester showed a characteristic pattern of optimum biogas production efficiency and performance when mixed with inoculum, which indicates its prospect for future evaluation and use.